Indoor navigation for the visually impaired by reading shop trademarks in shopping mall - Ling, Brandon Yi Yun (2022)

(untitled)
Indoor navigation for the visually impaired has been receiving much attention in recent years, and the increment of research or development related to the topic. The research and development of this system have played a vital role for the visually impaired to improvise a better future and improve their quality of life. Signs and labels are actively used for indoor navigation systems; however, these are not beneficial for the visually impaired. Due to their disabilities, it is difficult for the visually impaired to identify shop trademarks, obstacles, and shops in a shopping complex. As a result, this project aims to create a system that helps the visually impaired recognises trademarks, obstacles, and shops located in a shopping complex. Several components such as a camera, software application, and earbuds are required to execute the system. The camera will read images, which will then be processed by the software application recognising the character or object in the image. The information will then be converted to speech and delivered through earbuds or earphones. The project will have several limitations, which may result in the output not being very accurate such as the quality image and processing power of the device. Both issues contribute to the performance of the system and, therefore, the accuracy of navigation to be affected.